2010
DOI: 10.1073/pnas.1009205107
|View full text |Cite
|
Sign up to set email alerts
|

Diverse styles of submarine venting on the ultraslow spreading Mid-Cayman Rise

Abstract: Thirty years after the first discovery of high-temperature submarine venting, the vast majority of the global mid-ocean ridge remains unexplored for hydrothermal activity. Of particular interest are the world's ultraslow spreading ridges that were the last to be demonstrated to host high-temperature venting but may host systems particularly relevant to prebiotic chemistry and the origins of life. Here we report evidence for previously unknown, diverse, and very deep hydrothermal vents along the ∼110 km long, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
148
0
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(158 citation statements)
references
References 41 publications
8
148
0
2
Order By: Relevance
“…SUP05 is abundant in oxic/anoxic interfacial environments such as deep-sea hydrothermal plumes (Sunamura et al, 2004;Dick and Tebo, 2010;German et al, 2010), oxygen minimum zones (Stevens and Ulloa, 2008;Lavik et al, 2009;Walsh et al, 2009;Canfield et al, 2010) and symbioses with deep-sea bivalves (Newton et al, 2007). Our data set supports previous genomic studies that showed that members of this group are chemolithoautotrophic, obtaining energy by coupling sulfur oxidation to reduction of nitrate and/or oxygen (Newton et al, 2007;Walsh et al, 2009).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…SUP05 is abundant in oxic/anoxic interfacial environments such as deep-sea hydrothermal plumes (Sunamura et al, 2004;Dick and Tebo, 2010;German et al, 2010), oxygen minimum zones (Stevens and Ulloa, 2008;Lavik et al, 2009;Walsh et al, 2009;Canfield et al, 2010) and symbioses with deep-sea bivalves (Newton et al, 2007). Our data set supports previous genomic studies that showed that members of this group are chemolithoautotrophic, obtaining energy by coupling sulfur oxidation to reduction of nitrate and/or oxygen (Newton et al, 2007;Walsh et al, 2009).…”
Section: Discussionsupporting
confidence: 80%
“…Thus, little is known about the nature of plume microbial communities or their relationship to those of the seafloor or surrounding deep seawater. Several studies have reported the SUP05 group of sulfur-oxidizing Gammaproteobacteria in deep-sea hydrothermal plumes in widespread geographical locations (Sunamura et al, 2004;Dick and Tebo, 2010;German et al, 2010). Other prevalent microbial groups identified in plumes include Epsilonproteobacteria (Sunamura et al, 2004;Nakagawa et al, 2005;German et al, 2010), ammonia-oxidizing Betaproteobacteria (Lam et al, 2008), methanotrophs (Naganuma et al, 2004;Lam et al, 2008) and Marine Group I (MGI) archaea (Takai et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Located at 2,350-m depth on the Mid-Cayman Rise (13,14), hydrothermal fluids emanate from the Von Damm vent field at temperatures as high as 226°C (Fig. S1).…”
Section: Resultsmentioning
confidence: 99%
“…Surveys of the small subunit (SSU) ribosomal RNA (rRNA) genes using tag pyrosequencing and clone libraries have revealed the composition of plume microbial communities (Sunamura et al, 2004;Dick and Tebo, 2010;German et al, 2010;Sylvan et al, 2012). Metagenomic, metatranscriptomic and metaproteomic methods have provided insights into the roles of dominant organisms involved in oxidation of sulfur, hydrogen, methane and ammonia in hydrothermal plumes such as SUP05 Gammaproteobacteria , Methylococcaceae Gammaproteobacteria (Li et al, 2014a), Marine Group I Thaumarchaea (Baker et al, 2012) and SAR324 Deltaproteobacteria (Sheik et al, 2014).…”
Section: Introductionmentioning
confidence: 99%